2021
DOI: 10.3892/mmr.2021.12248
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofMelandrium firmumRohrbach on RANKL‑induced osteoclast differentiation and OVX rats

Abstract: Osteoporosis is a systemic skeletal disease characterized by reduced bone mineral density (BMD), which results in an increased risk of fracture. Melandrium firmum (Siebold & Zucc.) Rohrbach (MFR), 'Wangbulryuhaeng' in Korean, is the dried aerial portion of Melandrii Herba Rohrbach, which is a member of the Caryophyllaceae family and has been used to treat several gynecological conditions as a traditional medicine. However, to the best of our knowledge, the effect of MFR on osteoclast differentiation and osteop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…For example, ribosomal protein s5 was reported to serve as a potential target for inhibiting osteoclastogenesis (Chen et al, 2017), and ribosomal protein L29/HIP deficiency increased the fragility of adult bone in mice (Oristian et al, 2009). Actin is a type of cytoskeletal protein that plays important roles in muscle contraction, cell motility and maintenance of cellular shape (Kim et al, 2021). Some studies have also found that the expression of actin increases in the later stages of bone fracture healing, suggesting that it may be involved in the activities of osteoblasts and the remodeling of bone tissue (Li, Wang, et al, 2020; Matthews et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ribosomal protein s5 was reported to serve as a potential target for inhibiting osteoclastogenesis (Chen et al, 2017), and ribosomal protein L29/HIP deficiency increased the fragility of adult bone in mice (Oristian et al, 2009). Actin is a type of cytoskeletal protein that plays important roles in muscle contraction, cell motility and maintenance of cellular shape (Kim et al, 2021). Some studies have also found that the expression of actin increases in the later stages of bone fracture healing, suggesting that it may be involved in the activities of osteoblasts and the remodeling of bone tissue (Li, Wang, et al, 2020; Matthews et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TRAP is utilized as a serum marker to confirm the anti-osteoporotic effects in both animal experiments and an in vitro study ( 61 ). ALP is a marker expressed in the early stages of osteoblast differentiation ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…ALP is a marker of osteoblast activity and bone formation and is involved in osteoblast metabolism. Therefore, when bone metabolism is rapid, such as in conditions with metabolic bone disease, the activity of osteoblasts increases with excessive osteoclast activity, and the concentration of ALP in the serum increases ( Kuo and Chen, 2017 ; Kim M. et al, 2021 ). The ALP level in the OVX group increased compared to that in the sham group and decreased significantly in the SR-L group.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining is a staining method used to detect the presence of specific protein markers ( Duraiyan et al, 2012 ; Kim et al, 2020 ; Kim M. et al, 2021 ). In our study, the number of CTK-, NFATc1- and BMP-2-positive cells was evaluated by IHC staining.…”
Section: Discussionmentioning
confidence: 99%